(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study was aimed to assess the quality level of the sudanese standards and risks associated with the importation of Hatching Eggs as well as the sanitary measures in place based on the World Animal Health Organization (OIE) standards. Data were collected from the Federal Ministry of Animal Resources and Fisheries (FMARF), the Sudanese Standards and Metrology Organization (SSMO) and from (OIE). For that purpose risk assessment was used as described in Section 2 of the (OIE, 2009). The results showed that a total of (11,241,209) chicks, and (62,3070,30) layers and broilers hatching eggs were imported into the Sudan during the period 2005 – 2009 from 14 countries, which may comprise potential risk of introducing Avian Influenza (AI) and many other diseases into the country. In viewing the poultry health status in the exporting counties, the Avian Influenza is endemic in Egypt, which represented the main exporting country of the two commodities in 2005. In 2006 about 18.3% out of 235,626 (susceptible population) were infected with Avian Influenza (AI) and 43.2% out of that (susceptible population) were destroyed for the same reason. Moreover, the sudanese standards of hatching had not been set according to scientifically based risk estimations and the sanitary measures in place were less stringent to achieve the appropriate level of protection. Therefore, a multidisciplinary scientific risk analysis following OIE standards are recommended for the importation procedures and setting the Sudanese standards.